Sarguẕasht-i sāzmānhā va nihādhā-yi 'ilmīva āmūzishī dar Īrān - Ṣadrī Afshār, Ghulām Ḥusayn (Intishārāt-i Vizārat-i 'Ulūm va Āmūzish-i Ālī, 1971)
On educational and training institutes in Iran from the advent of Islam through 20th century.